Nitrates Evaluation in the National Térraba-Sierpe Wetland - Hernández-Alpízar, Laura; Mora-Molina, Jesús (Uniciencia, 2022)
This research aimed to describe, spatially and temporally, the concentrations of nitrates in correlation with anthropogenic activities surrounding the Sierpe River that crosses the National Térraba-Sierpe Wetland (HNTS). Although territorially protected by Costa Rican legislation, this wetland is surrounded by intense agricultural activity. In 2018, monthly monitoring of pH, nitrates, and dissolved oxygen was carried out in fourteen points of the river. A baseline around 5 mg NO3- / L was obtained in periods without agricultural activities and peaks up to 20 mg NO3- / L after fertilization activities. Correspondingly, a decrease in dissolved oxygen and pH was observed on days of high agricultural activity. In the months following fertilization, accelerated growth of aquatic plants and a general deterioration in mangrove reproduction were observed by collaborators of the HNTS management and surveillance program. Nevertheless, when high nitrates concentration in agricultural areas are observed, their decline is also observed in the direction of the river’s flow until it reaches its mouth. This facts shows the still active function of the wetland and its importance in the processing of nitrates. To regulate activities not only in the territorial limit but also in the limits of the water system surrounding the HNTS is recommended to protect this ecosystem function.